«Вечные темы» в юмористических рассказах Аркадия Аверченко - Polakowska, Ewa (Kultury Wschodniosłowiańskie – Oblicza i Dialog, 2018)
The paper describes the early period of Averchenko’s work. His stories were based on hilarious topics, humour and caricatures. The writer used all this means of expression very freely, easily, with a gentle tact and power of conviction, and what is even more important, with humour and wittily. During this period, he chose topics focused on a common big city life, stories of ordinary people, “new” trends in art, always up-to-date topic of man and woman, as well as relations between fathers and their children. Showing the portrait of a common citizen, the satirists laughed at defects of the contemporary world. This is how the particular humour Averchenko’s manifested.